Characterization of Congenital Syphilis Cases Reported in a Brazilian Region - da Silva, Jhenifer Cristina; Silva Santos, William Messias; Silva Santos, Jaqueline; Halboth, Nadia Veronica; Cardoso Maia, Maria Ambrosina (International Journal of Pediatrics and Child Health, 2019)
Congenital syphilis is a challenge for health services and its characteristics is an important area of study. This study identified the profile of congenital syphilis cases reported in an inland region of the state of Minas Gerais, Brazil, from 2012 to 2016. This is a descriptive historical cohort study from 2012 to 2016, and the data were from documentary sources. The study involved detailed analysis of the compulsory notification forms registered in the Information System on Diseases of Compulsory Declaration (SINAN). For data collection, researchers created a form for subsequent quantitative data analysis approach. The data obtained were tabulated and analyzed using simple descriptive statistics and shown in tables. The data were organized into five charts and separated based on: (1) number of cases notified; (2) information about mothers whose newborns have syphilis; (3) pregnancies that culminated in the birth of newborns with congenital syphilis, diagnosis and treatment of these mothers; (4) information about newborns with syphilis; (5) diagnosis, treatment, and outcome of these newborns. The researchers of this study believe that, by enabling the identification of the profile of congenital syphilis cases reported in a Brazilian region, the results may contribute to the development of health strategies to prevent and control syphilis in mothers and their children.